BAIAT DI ORGANISASI NAHDLATUL WATHAN DALAM TINJAUAN KOMUNIKASI INTRAPERSONAL - GUFRAN, M. (Universitas Islam Negeri (UIN) Mataram, 2021)
Baiat in the Nahdlatul Wathan organization is the oath of allegiance by Nahdlatul Wathan residents to the leader of the organization, namely the General Chairperson of the Nahdlatul Wathan (PBNW) Executive Board, through three stages, namely: 1) Preparation of allegiance, 2) Pronunciation of the contents of the oath of allegiance, and 3) Closing and prayer. This study aims to describe the baiat procession in the Nahdlatul Wathan organization in a review of intrapersonal communication. The method used in this research is descriptive qualitative method. The findings of this study are that baiat in the Nahdlatul Wathan organization is an intrapersonal communication, where the four stages in intrapersonal communication, namely sensation, perception, memory, and thinking can be seen in the motivation to take allegiance, the intention to take allegiance, certain considerations before taking allegiance, the reasons for taking allegiance, the urgency of taking baiat. , the benefits of taking baiat, awareness of the purpose of baiat, awareness of taking baiat, understanding the contents of baiat, the belief to carry out baiat, thinking about the consequences of taking baiat, contemplating the meaning of baiat, the state of the heart after taking baiat, and the role of baiat in attitude and action.